Challenges for quality management in implementation, maintenance, and sustainability of research tissue biobanks - Schmitt, Susanne; Kynast, Katharina; Schirmacher, Peter; Herpel, Esther (Virchows Archiv, 2016)
Availability of high-quality human tissue samples and access to associated histopathological and clinical data is essential for basic and translational biomedical research, especially in areas of personalized medicine, drug, and biomarker development and mechanistically oriented biomedical research projects. Therefore, it is pivotal to establish and maintain quality-assured tissue biobanks that provide high-quality biomaterial to research thereby increasing the impact and reliability of scientific results.
Published online: 14 August 2015
Gesehen am 19.05.2020